Diverging Views on Zero Budget Natural Farming (ZBNF): Insights from Farmers in Northern Karnataka - Patil, Dayananda; Jha, S K; Bellagi, Rahul Dundesh; Priyanka, B N; Gunashekhar, H; Patil, N D Chethan (Indian Journal of Extension Education, 2024)
Zero Budget Natural Farming (ZBNF) is promoted as an alternative farming method to achieve sustainability and build a climate-resilient agricultural system. The perception of farmers towards ZBNF determines its adoption. For the study was conducted in 2020 two districts of Northern Karnataka were chosen and respondents were categorised into adopters, planners, and non-adopters. From each group, 50 respondents were selected. The Kruskal-Wallis test was conducted to test the significant difference followed by the post hoc Dunn-Bonferroni test. Significant differences were found in 13 out of 15 statements, particularly concerning the necessity of indigenous cattle (H = 16.71, p < 0.001), labour intensity (H = 17.59, p < 0.001), and the reduction in yield during the first year of ZBNF (H = 32.16, p < 0.01). Planners and adopters differed significantly on statements such as ZBNF’s labour-intensive nature (p = 0.006) and its independence from heavy machinery (p = 0.003). The Dunn-Bonferroni post hoc test highlighted differences across three groups on statements like all types of crops can be cultivated in ZBNF and there is no pesticidal residual effect of ZBNF products on human health. These distinct perceptions highlight the need for targeted outreach strategies based on farmers’ perception.
Keywords: ZBNF; Perception; Planners; Adopters; Non-adopters